Weaving knowledge: Extension project for elderly women learners - Pereira Battisti, Francisleth (2023)
This paper aims to present some results obtained from an extension project entitled "Weaving Futures", which was held by the Catarinense Federal Institute (IFC). The methodological approach used in this project was descriptive and qualitative research, in addition to an experience report. The project "Weaving Futures" aimed to use fashion as a tool for promoting social change, and it had elderly women under vulnerable conditions as its target audience. This segment of population was supported by the Reference Center for Social Assistance (CRAS), in Ibirama, Santa Catarina. The project used workshops to teach those participants some fashion techniques which could be made without any machinery. The main objective of this extension project was to improve quality of life for those women, as well as being a welcoming, learning environment, and a space for hearing their voices. We also sought to reflect on the importance of this extension project in their lives, understanding its benefits and the opportunity for interaction among the participants. The results indicate that the workshops were understood by the participants as an essential environment for social dynamics, providing them strengthening of social ties, autonomy, knowledge acquisition, fun, and self-esteem.